ANALISIS PERILAKU KONSUMEN DALAM MEMBELI BIBIT BUAH DI KOTA BATURAJA KABUPATEN OKU - elena elena; fifian permatasari; putri ayu ogari (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
The purpose of this study was to analysis consumer behavior in buying fruit The data collection location research held on month December 2018. Method The research in is Method Surveys. Method data used in research this is Interview with questionnaire as tool data collection. The data used is the primary data is seeds. Collection methods include primary and secondary. Sampling method uses incendetal sampling. Based on the results of the research conducted, it can be concluded that consumer preferences for the three types of fruit seeds at the kiosks selling various frut seeds of kelengkeng and guava seeds that are preferred by both are moe favored han are preferred by both are more favored than mango seedlings because the Q Cochran value is 8,5 ≥ 0.05(2) which is equal to 5,991 so H0 rejected.Keywords : Consumer, fruit seeds